Effective Control Scheme of PWM Universal Motor with Coulomb Friction based on Particle Swarm Optimization - Kammogne, A. Soup Tewa; Tchaptchet, M. Njamen; Siewe, M. Siewe; Louodop, P.; Kenne, G. (Journal of Applied Nonlinear Dynamics, 2026)
Power electronic converters have undesirable characteristics that can be influenced by the structure of the converter, the load, the parameters as well as the pulse period, which leads to the malfunction of the converters. For precise positioning tasks, the friction phenomenon plays an important role. In this paper, we first propose to study the dynamics of the general period-1 behavior in a PWM-controlled universal DC motor drive system with nonlinear Coulomb friction and subsequently control the system towards period 1 by optimizing the controller parameters via the particle swarm algorithm (PSO). The dynamic analysis is performed using bifurcation tools, and phase portraits showing that the system exhibits very rich and striking behavior such as periodic orbits, period-doubling bifurcation, quasi-periodicity and chaos control in live mode. In addition, the Filippov method is used to calculate the eigenvalues of the monodromy matrix belonging to the whole system. Finally, the results of the numerical simulation are in almost perfect agreement with the analog results obtained with PSIM. The results obtained in this work have not yet been reported in the literature to the best of the author’s knowledge and therefore deserve to be disseminated.